Antihypertensive agents: a long way to safe drug prescribing in children - Nida Siddiqi (14150598) (2019)
Recently updated clinical guidelines have highlighted the gaps in our understanding and management of pediatric hypertension. With increased recognition and diagnosis of pediatric hypertension, the use of antihypertensive agents is also likely to increase. Drug selection to treat hypertension in the pediatric patient population remains challenging. This is primarily due to a lack of large, well-designed pediatric safety and efficacy trials, limited understanding of pharmacokinetics in children, and unknown risk of prolonged exposure to antihypertensive therapies. With newer legislation providing financial incentives for conducting clinical trials in children, along with publication of pediatric-focused guidelines, literature available for antihypertensive agents in pediatrics has increased over the last 20 years. The objective of this article is to review the literature for safety and efficacy of commonly prescribed antihypertensive agents in pediatrics. Thus far, the most data to support use in children was found for angiotensin-converting enzyme inhibitors (ACE-I), angiotensin receptor blockers (ARB), and calcium channel blockers (CCB). Several gaps were noted in the literature, particularly for beta blockers, vasodilators, and the long-term safety profile of antihypertensive agents in children. Further clinical trials are needed to guide safe and effective prescribing in the pediatric population. Other Information Published in: Pediatric Nephrology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00467-019-04314-7